IMPLEMENTATION OF THE POLICY PROVIDING ADDITIONAL EMPLOYEE INCOME (TPP) IN THE GENERAL SECTION OF THE REGIONAL SECRETARIAT OF TOLI TOLI DISTRICT - Susanti, Ani; Khairunnisa, Khairunnisa; Nuraisyah, Nuraisyah (CV. Lafadz Jaya, 2024)
The purpose of this study was to determine the Implementation of the Policy for Providing Additional Income Allowances for State Civil Servants at the Regional Administration Bureau and Regional Secretariat Government of Toli-toli Regency. The research method used is qualitative. The location of the research was carried out at the Regional Administration Bureau and Government of the Regional Secretariat of Toli-toli Regency with 5 informants. Data collection is carried out by conducting interviews, observation, and documentation. The data analysis technique uses Miles and Huberman's Interactive Model. The main theory that is used as a reference in this study is Edward III's theory (1980-9) which explains that there are 4 aspects that can be used as measurements of policy implementation, namely communication factors, resources, dispositions, and bureaucratic structures. Based on the results of the research, it shows that the Implementation of the Policy for Providing Additional Income Allowances for ASN at the General Section of the Regional Secretariat of Toli Toli Regency, has not been running effectively, seen from several aspects, namely: ( 1) policy communication has several dimensions, namely the dimensions of transmission, clarity, and consistency, but everything is not going well. Communication carried out by the leadership and implementing staff at the General Section of the Regional Secretariat of Toli Toli Regency, showed results that were not optimal. (2) human resources in carrying out administration are already in the professional category and budgetary resources and facilities are adequate, (3) The disposition of staff placement is in accordance with their areas of expertise, (4) The SOP structure is clear and implemented effectively by monitoring or supervision and strict sanctions against ASN who commit violations. The conclusion is that communication, resources, disposition, and bureaucratic structure can be implemented effectively.